ANALISIS PERKEMBANGAN KEMAMPUAN KEUANGAN DAERAH PADA PEMERINTAH DAERAH KABUPATEN SANGGAU - B21109004, Yuli Anggraeni (Jurnal Pembangunan dan Pemerataan, 2015)
Regional autonomy policy basically is a delegation of authority from the central government to the local government to regulate and manage its own government and society according to their local needs and capacity. The policy was companied by the delegation of authority to regulate and manage regional finance through the fiscal decentralization. The capability of regional finance is the ability of regional government in improving local own source revenue (PAD) that leads to the independence of regional finance which is measured by fiscal decentralization. The aim of this study is to analyze the development of local government of Sanggau regency’s financial ability. The method used in this study is descriptive study. The data source used secondary data. The data collection techniques used in this study consists of: (1) ratio degree of fiscal decentralization, (2) ratio of independence, (3) ratio routine of capability index. Based on the results of analysis, showed that: (1) the capability rate of regional finance in the government of Sanggau regency for 5 (five) fiscal years viewed by the degree of fiscal decentralization is still very low. It showed by the proportion rate of local own source revenue (PAD) 3.85% (very low), proportion rate of BPHP 6.31% (very low), and proportion rate of donations 73.62% (very low). It is showed that regional finance is still depends on central government. (2) The independence ration of regional finance showed development of fluctuation with the average rate 4.38% (very low). It shows that the capability of regional finance of Sanggau regency’s government in funding all of the activities is still depends on other sources beside PAD. (3) The ratio routine of capability index showed development of fluctuation with the average rate 5.3% (very low). It shows that the routine capability of Sanggau regency’s government I funding all of the activities is still depends on other sources beside PAD. It means that PAD has the low capability in funding its routine expenses.   Keyword;  Local Financial Capacity, Ratio Degree of Fiscal Decentralization, Ratio of Independence, Ratio Routine of Capability Index